STUDENTS’ PERCEPTION OF THE USE OF SOCIAL MEDIA FOR LEARNING ENGLISH DURING COVID 19 PANDEMIC - Nurrahmi Nurrahmi; Maemuna Muhayyang; Geminastiti Sakkir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This qualitative study examines students' perceptions of using social media for English language learning during the COVID-19 epidemic. It collects data using a descriptive qualitative method. Up to thirty students in classes A, B, C, D, and E of the fourth semester of the English Education Study Program at the Faculty of Languages and Literature of the State University of Makassar participated in this study. To choose individuals, this study used purposeful sampling. The result shows that students utilize social media more frequently. Claims that more time is spent on social media when students are cooped up at home and have more spare time lend credence to this. Students also have a positive perception of social media's role in English language acquisition. Twitter and Instagram are the most widely used social media platforms for learning English in receptive skills, listening skills, and reading skills. These programs were chosen because, thanks to their widespread use, they have access to a never-ending supply of English input. According to the findings of data analysis of interview transcripts on students' usage of social media for English language learning during the COVID-19 epidemic, they claimed that the sites offer an infinite supply of English information, allowing them to keep improving their receptive skills. Students feel comfortable and eager to learn English outside of school because of the situation, which provides a stress-free language environment for them.